The Impact of the physical environment on residents' self-rated health : a case study in Penang, Malaysia / Massoomeh Hedayati, Aldrin Abdullah and Mohammad Javad Maghsoodi Tilaki - Hedayati, Massoomeh; Aldrin, Abdullah; Maghsoodi Tilaki, Mohammad Javad (Universiti Teknologi MARA, Perak, 2019)
There is continous debate on the impact of house quality on residents’ health and well-being. Good living environment improves health, and fear of crime is recognised as a mediator in the relationship between physical environment and health. Since minimal studies have investigated the relationship, this study aims to examine the impact of the house quality on fear of crime and health. A total of 230 households from a residential neighbourhood in Malaysia participated in the study. Using structural equation modelling, the findings indicate that housing quality and fear of crime can account for a proportion of the variance in residents’ self-rated health. However, there is no significant relationship between housing quality and fear of crime. Results also show that fear of crime does not mediate the relationship between housing quality and health. This study suggests that the environment-fear relationship should be re-examined theoretically.